Corporate social responsibility and corporate financial fraud: evidence from China - Wang Gen; Andi Ina Yustina; Andrianantenaina Hajanirina; Mila Austria Reyes (President University Press, 2022)
With the development of globalization, corporate social responsibility has become a hot subject of shared concern for all nations in the globe. The lack of CSR performance in modern China has prompted worries about CSR in both academic and practical circles in China. In this work, the authors continue Liao's research and seek to re-analyze if CSR is connected to financial fraud. Through the analysis of A-share companies in the construction industry listed on the Shanghai Stock Exchange and the Shenzhen Stock Exchange, this paper finds that CSR scores are negatively correlated with financial fraud activities, which suggests that CSR companies are less likely to engage in financial fraud. Thus, to some degree, it may also argue that CSR is an ethical activity that has the power to minimize corporate financial misbehavior.